A viabilidade do acordo de leniência como ferramenta de proteção ambiental - Dall' Acua, Monique Maria de Oliveira (My University, 2026)
This dissertation explores the possibility of expanding and investigating the feasibility of applying leniency agreements in the environmental field in Brazil to address environmental issues. To this end, we examine the perspectives of antitrust, compliance, ESG governance, and the Brazilian Anti-Corruption Law. The study analyzes the relationship between competition and environmental protection, highlighting how anti-competitive practices can negatively impact sustainability by limiting innovation and perpetuating polluting production models. Environmental compliance is presented as an instrument of corporate governance, encouraging ethical and transparent business practices. The research highlights the Anti-Corruption Law (Law No. 12.846/2013) and its role in environmental oversight and in combating corruption in environmental licensing and inspection. Leniency agreements emerge as a strategic mechanism to stimulate business cooperation, potentially serving as an instrument for preventing infractions and promoting sustainability. [resumo fornecido pelo autor]
A dissertação explora a possibilidade da expansão investiga a viabilidade da aplicação o acordos de leniência na seara ambiental no Brasil. Para tanto perpassamos sob a ótica do antitruste, compliance, governança ESG e da Lei Anticorrupção Brasileira. O estudo analisa a relação entre a concorrência e a proteção ambiental, destacando como práticas anticoncorrenciais podem impactar negativamente a sustentabilidade ao limitar a inovação e perpetuar modelos produtivos poluentes. O compliance ambiental é apresentado como um instrumento de governança corporativa, incentivando práticas empresariais éticas e transparentes. A pesquisa destaca a Lei Anticorrupção (Lei nº 12.846/2013) e seu papel na fiscalização ambiental e no combate à corrupção em licenciamento. Os acordos de leniência surgem como mecanismo estratégico para estimular a cooperação empresarial, podendo ser instrumento de prevenção de infrações e promoção de sustentabilidade. [resumo fornecido pelo autor]
Keywords: Direito ambiental; Proteção ambiental; Gestão ambiental; Sustentabilidade; Environmental law; Environmental protection; Environmental management; Sustainability